Morphological characterization and habitat suitability modeling of the goat population of Benin under climate change scenarios - Whannou, Habib Rainier Vihotogbe; Afatondji, Cossi Ulriche; LINSOUSSI, AGOSSA CÔME; FAVI, Gnimanssou Abraham; Nguyen, Thanh Thi; HOUINATO, MARCEL ROMUALD BENJAMIN; DOSSA, HIPPOLYTE GBÉNAKPON LUC HIPPOLYTE (My University, 2022)
Background: Insufcient knowledge of the genetic and phenotypic diversity in the local Beninese goat population combined with the lack of understanding of its adaptive capacity to ongoing environmental and societal changes hampers the development of strategies for better management and genetic improvement. The objective of this study was to establish the current geographical distribution of goats in Benin based on their morphology and model the potential habitat suitability of the three known main goat phenotypes (i.e., Djallonké goat or Type I, Sahelian goat or Type II, and their Crossbreeds or Type III) under climate change scenarios. Ten qualitative and 26 linear body measurements were taken on 2114 adult female goats sampled across the three vegetation zones of the country. Fifteen ratios were generated from the quantitative variables. The data were analyzed using generalized linear model procedures followed by multiple comparisons of least-squares means and multivariate analytical methods, including canonical discrimination analysis and hierarchical ascendant classifcation. Each goat was then assigned to one of the three aforementioned main goat phenotypes following its morphological characteristics and according to the a priori cluster membership defned in the previous step. The Maximum Entropy algorithm was used to model the current and future distribution of the three goat phenotypes under climate change scenario using the Representative Conservation Pathways 4.5 and 8.5. Results: All linear body measurements varied among vegetation zones. In the discriminant function analysis, 71% of the measured individuals were correctly classifed in their vegetation zone of origin by seven measured variables and three ratios. The cluster procedure analysis revealed two groups of goats subdivided into the three main phenotypes. The modeling results showed that the currently highly favorable habitats were distributed in the South for Type I, in the North for Type II, and both South and North for Type III. However, under climate change scenarios, the favorable habitats for Type I decreased while those of Types II and III increased Conclusions: The results of this study confrm the spatial variation of the goat population in Benin. The habitat suitability model can be used to support decision-making toward better management of goat genetic diversity in Benin.
Keywords: Capra hircus; Climate change; Ecological niche modeling; Farm animal species; MaxEnt model; Morphology